Pengaruh Beban Kerja, Insentif, Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Dinas Sosial Kabupaten Majalengka - Rinrin Asyifa Lutpiah; Syarifuddin Syarifuddin (RELASI : JURNAL EKONOMI, 2023)
The purpose of this study is to find out and analyze how the level of workload, incentives, and non-physical work environment on the performance of the employees of the Majalengka Regency Social Service, and the magnitude of the influence of workload, incentives, and non-physical work environment partially and simultaneously on the performance of the employees of the District Social Service. Majalengka. This study uses quantitative methods and descriptive analysis as well as multiple regression analysis using SPSS 26. The sampling technique used is a saturated sample, namely all 33 employees of the Majalengka Regency Social Service. and the performance of the crew is in the very good category. Partially, the workload and incentives have a significant effect while the non-physical work environment has no significant effect on the performance of the employees of the Majalengka Regency Social Service. The magnitude of the effect of workload, incentives, and non-physical work environment is 75.2% while the remaining 24.8% is influenced by other variables not examined in this study.